The Effect of Percutaneous Coronary Intervention on Patients with Acute Myocardial Infarction and Cardiogenic Shock Supported by Extracorporeal Membrane Oxygenation - Yan Wang; Hongfu Fu; Jin Li; Haixiu Xie; Chenglong Li; Zhongtao Du; Xing Hao; Hong Wang; Liangshan Wang; Xiaotong Hou (Reviews in Cardiovascular Medicine)
Background: Patients suffering from acute myocardial infarction complicated by cardiogenic shock (AMICS), who undergo veno-arterial extracorporeal membrane oxygenation (VA-ECMO) therapy, typically exhibit high mortality rates. The benefits of percutaneous coronary intervention (PCI) in these patients remains unclear. This study aims to investigate whether PCI can mitigate mortality among patients with AMICS supported by ECMO. Methods: Data from patients ≥18 years, who underwent VA-ECMO assistance in China between January 1, 2017, and June 30, 2022, were retrieved by searching the Chinese Society of Extracorporeal Life Support (CSECLS) Registry. A total of 1623 patients were included and categorised based on whether they underwent PCI. Using propensity score matching, 320 patient pairs were successfully matched. The primary outcome was in-hospital mortality rate. The secondary outcomes included VA-ECMO duration, Hospital stay, ECMO weaning and ECMO related complications. Results: In the cohort of 1623 patients, 641 (39.5%) underwent PCI. Upon conducting multivariate logistic regression analysis, it was observed that those who underwent PCI had a lower prevalence of hyperlipidemia (13.1% versus [vs.] 17.8%), chronic respiratory disease (2.5% vs. 4.3%) and lower lactic acid (5.90 vs. 8.40). They also had a more significant history of PCI (24.8% vs. 19.8%) and were more likely to be smokers (42.6% vs. 37.0%). Patients in the PCI group exhibited lower in-hospital mortality before and after matching (40.3% vs. 51.6%; p = 0.005), which persisted in multivariable modeling (adjusted odds ratio [aOR]: 0.69; 95% confidence interval 0.50–0.95; p = 0.024). Patients who received PCI were more successfully weaned from ECMO (88.6% vs. 75.8% before matching). PCI was not a risk factor for ECMO related complications. Conclusions: Among patients who received ECMO support for AMICS, PCI was associated with a lower rate of in-hospital mortality.